2007
DOI: 10.1210/en.2007-1097
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Subcellular Evidence for Neuronal Interaction between the Chemokine Stromal Cell-Derived Factor-1/CXCL 12 and Vasopressin: Regulation in the Hypothalamo-Neurohypophysial System of the Brattleboro Rats

Abstract: We previously described a colocalization between arginine vasopressin (AVP) and the chemokine stromal cell-derived factor-1alpha (SDF-1) in the magnocellular neurons of both the hypothalamic supraoptic and paraventricular nucleus as well as the posterior pituitary. SDF-1 physiologically affects the electrophysiological properties of AVP neurons and consequently AVP release. In the present study, we confirm by confocal and electron microscopy that AVP and SDF-1 have a similar cellular distribution inside the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Immunohistochemical analysis of CXCL12 and CXCR4 labeling in the RN by confocal microscopy indicates that these immune proteins are expressed as discrete puncta in the cytoplasm and outer membrane of 5-HT cell bodies and processes. The punctate staining pattern has been observed for CXCL12 and CXCR4 in previous immunohistochemistry studies in various brain regions (Banisadr et al, 2002; Banisadr et al, 2003; Rostasy et al, 2003; Miller et al, 2005; Callewaere et al, 2008; McCandless et al, 2008) including the DRN (Banisadr et al, 2002; Banisadr et al, 2003; Callewaere et al, 2008) as well as in the periphery (Hu et al, 2007). …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Immunohistochemical analysis of CXCL12 and CXCR4 labeling in the RN by confocal microscopy indicates that these immune proteins are expressed as discrete puncta in the cytoplasm and outer membrane of 5-HT cell bodies and processes. The punctate staining pattern has been observed for CXCL12 and CXCR4 in previous immunohistochemistry studies in various brain regions (Banisadr et al, 2002; Banisadr et al, 2003; Rostasy et al, 2003; Miller et al, 2005; Callewaere et al, 2008; McCandless et al, 2008) including the DRN (Banisadr et al, 2002; Banisadr et al, 2003; Callewaere et al, 2008) as well as in the periphery (Hu et al, 2007). …”
Section: Discussionsupporting
confidence: 54%
“…In previous electron microscopy studies of the rat posterior pituitary, vasopressinergic neurons were shown to contain CXCL12 in dense-core vesicles (Callewaere et al, 2008). Furthermore, although cellular processes were not stained for specific axonal or dendritic markers, the localization of CXCR4 in the outer membrane and processes of 5-HT neurons suggests that CXCL12’s interactions with CXCR4 may have a role in 5-HT mediated synaptic transmission (Limatola et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…In the central nervous system (CNS), chemokines are detected in glial cells and neurons (Miller et al 2008). Chemokines can act as neuromodulators through their receptors in the healthy CNS, namely in spinal cord (Gosselin et al 2005), hypothalamus (Callewaere et al 2008) and the nigrostriatal pathway (Skrzydelski et al 2007). We recently observed that the chemokine CCL2 enhances striatal DA release and locomotion (Guyon et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that potential effects of Cd might include exaggerated synthesis of AVP during Cd exposure in our model Meriones shawi and support the idea of an increase of AVP as result of Cd intoxication (see figure 2 and 3). These findings suggest that Cd ingestion has potential effects on the vasopressinergic system that responds with elevated synthesis of AVP under stimulated conditions [57]. A large number of studies have demonstrated that Cd exposure produce marked neuroendocrine changes in animals [58][59] and human [60].…”
Section: Effect Of CD On Water Metabolismmentioning
confidence: 96%